INOVASI PEMBELAJARAN DI KELAS MELALUI OPTIMALISASI PLATFORM MERDEKA MENGAJAR OLEH GURU - Rosyidah, Aminatur Rosyidah; Elok Hidayah; Faridatul Amanah (JEAS (Journal of Educational and Applied Science), 2024)
Learning innovation is one of the main keys in improving the quality of education in the digital era. This research aims to examine the utilization of Merdeka Mengajar platform by teachers as an innovative effort in the learning process in the classroom. This platform is designed to give teachers the freedom to design and implement learning that is more creative, adaptive, and in accordance with student needs. Through a descriptive qualitative approach, this study analyzes how the role of the Merdeka Mengajar Platform can assist teachers in supporting the implementation of the independent curriculum and find out how teachers use the features in the platform to create a more interactive and student-centered learning atmosphere. The results show that Merdeka Mengajar Platform helps teachers design more varied learning methods, provide wider access to materials, and increase student involvement in the learning process. In addition, this platform also supports collaboration between teachers and the continuous development of teacher professionalism. Thus, the use of Merdeka Mengajar has the potential to be an innovative solution in overcoming learning challenges in the digital era, especially in the context of independent and comprehensive learning.